1984
DOI: 10.1016/0301-5629(84)90195-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic duplex scanning in atherosclerotic disease of the innominate, subclavian and vertebral arteries. A comparative study with angiography

Abstract: Abstract-Ultrasonic duplex scanning of the vertebral artery has a sensitivity of 0.80 and a specificity of 0.83 for the detection of an obstructive lesion of 50% or more at the site of the ostium. For the subclavian arteries these values are respectively 0.73 and 0.91. For both vessels the test has a very high negative predictive value of respectively 0.96 and 0.97. Therefore duplex ultrasound scanning is a reliable test in screening patients suspected of multi-level atherosclerotic disease of the extracranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Moreover, the duplex scan did not satisfactorily display the ostium of 28 vertebral arteries. In contrast to Ackerstaff et al, 4 using duplex sonography Touboul et al 7 were able to visualize the pretransverse and intertransverse segments in all of 50 healthy subjects. The ostium was seen in 47 persons on the right side and in 30 on the left.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the duplex scan did not satisfactorily display the ostium of 28 vertebral arteries. In contrast to Ackerstaff et al, 4 using duplex sonography Touboul et al 7 were able to visualize the pretransverse and intertransverse segments in all of 50 healthy subjects. The ostium was seen in 47 persons on the right side and in 30 on the left.…”
Section: Discussionmentioning
confidence: 80%
“…Acker- staff et al 4 reported that 31 of 117 vertebral arteries studied could not be identified with the duplex scanning system. Moreover, the duplex scan did not satisfactorily display the ostium of 28 vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler samples were taken and Peak Systolic Velocity (PSV) was recorded. Criteria used for grading ≥50% stenosis were focal elevated blood flow velocity with a PSV cut-off point at the V1 segment of the vertebral artery of 140 cm/s and 125 cm/s at the V2 segment (Ackerstaff et al, 1984(Ackerstaff et al, , 1988Hua et al, 2009;Koch, Romano, Park, Amir, & Forteza, 2009). …”
Section: Duplex Ultrasonographymentioning
confidence: 99%
“…Previous studies concerning the quantification of proximal VA stenosis by ultrasound are not recent and are limited in number [10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. They used continuous-wave Doppler sonography [13, 21]and Duplex scanning [10, 11, 12, 14, 15, 18, 19]without color Doppler.…”
Section: Discussionmentioning
confidence: 99%
“…They used continuous-wave Doppler sonography [13, 21]and Duplex scanning [10, 11, 12, 14, 15, 18, 19]without color Doppler. Only 5 recent papers have used color-coded Doppler for examination of the vertebral arteries [16, 17, 20, 22, 23].…”
Section: Discussionmentioning
confidence: 99%